2017
DOI: 10.1103/physrevc.95.034331
|View full text |Cite
|
Sign up to set email alerts
|

Structure and decay of the pygmy dipole resonance in Ne26

Abstract: The low-lying spectra of 24,25,26 Ne and the structure of the pygmy dipole resonance (PDR) in 26 Ne have been theoretically studied by the antisymmetrized molecular dynamics (AMD) and its extended version called shifted-basis AMD. The calculated energy and strength of the PDR reasonably agree with the observation, and the analysis of the wave function shows that the PDR is dominated by neutron excitation coupled to the quadrupole excited core nucleus 25 Ne, which explains the observed unexpected decay of PDR t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 67 publications
(217 reference statements)
0
15
0
Order By: Relevance
“…One candidate is 24 Mg, where it has been suggested that some peaks of the ISGMR strength are due either to 20 Ne + α, or to 12 C + 12 C vibrations, or even to a more exotic vibration of a pentagon of α clusters (with an additional α lying in the center) [81]. Similar predictions have been made for some of the peaks appearing the ISGDR strength of 20 Ne and 44 Ti [82] (see also [83,84]).…”
Section: Cluster Modelsmentioning
confidence: 67%
“…One candidate is 24 Mg, where it has been suggested that some peaks of the ISGMR strength are due either to 20 Ne + α, or to 12 C + 12 C vibrations, or even to a more exotic vibration of a pentagon of α clusters (with an additional α lying in the center) [81]. Similar predictions have been made for some of the peaks appearing the ISGDR strength of 20 Ne and 44 Ti [82] (see also [83,84]).…”
Section: Cluster Modelsmentioning
confidence: 67%
“…Main interest are properties of the IS LED modes such as the cluster and vortical aspects. For this aim, we apply the method of the shifted basis AMD (sAMD) [43][44][45] combined with the cluster generator coordinate method (GCM). The sAMD+GCM has been recently constructed to describe both the single-particle excitation and large amplitude cluster mode.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] and Refs. [10,11] for review articles) and their complex nature has been extensively discussed and interpreted in terms of oscillations of a neutron skin against a core, mixing of isoscalar and isovector nature, coupling with a toroidal motion, single-particle versus collective behavior, deformation effects (see for instance some recent publications [12][13][14][15][16][17][18][19][20][21][22][23]). Experimental evidence on the existence of low-energy excitations related to a neutron excess was also reported in Refs.…”
Section: Introductionmentioning
confidence: 99%